Social Networks, Ethnicity, and Entrepreneurship - William R. Kerr; Martin Mandorff (Center for Economic Studies and ifo Institute (CESifo), 2016)
We study the relationship between ethnicity, occupational choice, and entrepreneurship. Immigrant groups in the United States cluster in specific business sectors. For example, the concentration of Korean self-employment in dry cleaners is 34 times greater than other immigrant groups, and Gujarati-speaking Indians are similarly 108 times more concentrated in managing motels. We develop a model of social interactions where non-work relationships facilitate the acquisition of sector-specific skills. The resulting scale economies generate occupational stratification along ethnic lines, consistent with the reoccurring phenomenon of small, socially-isolated groups achieving considerable economic success via concentrated entrepreneurship. Empirical evidence from the United States supports our model's underlying mechanisms.
Keywords: L26; D21; D22; D85; F22; J15; L14; M13; 330; entrepreneurship; self-employed; occupation; ethnicity; immigration; networks